A comparison of clinical, hepatic and immunological effects of three different parenteral lipid emulsions in children - Çakır, Salih Çağrı; Özkan, Tanju; Özgür, Taner (The European Research Journal, 2020)
Objectives: Lipid emulsions are not only considered as a source of energy, but also as a regulatory substance for key metabolic functions in different diseases. The aim of the present study was to compare clinical, biochemical and immunological effects of olive oil, soybean oil and omega-3 fatty acid which are administrated to the children in parenteral nutrition products.Methods: Patients who were admitted to pediatric intensive care unit and had parenteral nutrition for 7 days are included in the study. The patients were randomised into 3 groups based on the admission order, including 10 patients in each group. The children in Group O were fed by a lipid emulsion based on olive oil; the children in Group S were fed by a soybean based lipid emulsion and the children in group F were fed by soybean based lipid emulsion with omega-3 based solution. Analysis were made on the first and the seventh day. Laboratory parameters as well as hemogram, biochemical analysis, immunoglobulins, lymphocyte subgroup panel and cytokine levels were evaluated just before parenteral nutrition (day 0, basal value) and at day 7 of parenteral nutrition. Clinical monitoring parameters included body weight, and circumference of the mid-upper arm.Results: Thirty children were enrolled into the study. Total cholesterol and triglyceride levels significantly increased in Group O whereas triglyceride level significantly increased in Group S. Hemogram, liver function tests, cytokine levels, lymphocyte sub-group distribution, immunoglobulin levels and total antioxidant capacity measurements were not different.Conclusions: Three lipid emulsions which are used for parenteral nutrition treatment in intensive care unit patients are clinically and biochemically useful.